Fast iron oxide-induced low-field magnetic resonance imaging. (22nd October 2020) - Rodriguez, Gonzalo G; Erro, Eustaquio M; Anoardo, Esteban
Abstract: Dynamic images acquired by proton fast field-cycling magnetic resonance imaging are presented for the first time. Image contrast mediated by superparamagnetic iron oxide nanoparticles and weighted by the spin-lattice (T1 ) relaxation time, and both spin-lattice and spin-spin (T2 ) relaxation times, are discussed. Image acquisition and processing within 8 s is allowed for real-time recording of exemplary physical situations evolving in a compatible time-scale. Two simple examples are shown with the corresponding videos assembled by sequencing the acquired images. Fast iron oxide-induced low-field magnetic resonance imaging (MRI) constitutes the first step in the development of field-cycling functional MRI for biomedical and physical applications.